Sal (Shorea robusta) Natural Regeneration De-novo. Effect of Soil Working and Weeding on the Growth and Establishment - Qureshi, I. M.; Srivastava, P. B. L.; Bora, N. K. S. (Indian Forester, 1968)
An investigation was conducted to study the effect of weeding and soil working on the growth and establishment of natural regeneration of sal resulting from a profuse seed crop in 1963 in the F.R.I. Estate. Plots were laid out in three varying light conditions ,viz., (i) in the open, (ii) in partial shade, and (iii) in sal plantations in Demonstration Area. Regular treatments of weeding and soil working were given and survival, height growth and dying-back of seedlings recorded. Besides, moisture and light variations were also measured. The results indicate that both these cultural operations, viz., weeding and soil working are most beneficial in respect of growth and survival of the seedlings in the open and in the partial shade. In the open soil moisture appears to be limiting factor as the growth showed marked improvement in height with weeding and soil working. And since some of the seedlings were putting on vigorous growth their requirements of moisture and nutrient. Resulted in so-to-say 'natural thinning' of the excess number of seedlings with reference to a particular site. In the plantations, the comparatively poor light conditions appear to be responsible for the poor growth and survival though the soil moisture was in no way deficient particularly in weeded and soil worked plots as compared to the other two categories of plots. In partial shade, both soils moisture and light conditions were favourable resulting in both better growth and survival of seedlings. It is concluded that ideal light conditions have to be synchronised with these cultural operations in order to get the best results.